2020
DOI: 10.3390/pathogens9120981
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Introductions and Predominance of Rotavirus Group A Genotype G3P[8] in Kilifi, Coastal Kenya, 4 Years after Nationwide Vaccine Introduction

Abstract: Globally, rotavirus group A (RVA) remains a major cause of severe childhood diarrhea, despite the use of vaccines in more than 100 countries. RVA sequencing for local outbreaks facilitates investigation into strain composition, origins, spread, and vaccine failure. In 2018, we collected 248 stool samples from children aged less than 13 years admitted with diarrheal illness to Kilifi County Hospital, coastal Kenya. Antigen screening detected RVA in 55 samples (22.2%). Of these, VP7 (G) and VP4 (P) segments were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(123 reference statements)
1
8
2
Order By: Relevance
“…Our findings are in concordance with reports of African countries such as Botswana and Kenya in which G3P [4] was found after rotavirus vaccine introduction [42,43]. However, some studies reported G3P [8] in high frequency in cases of MSD in the post-vaccine introduction period in Mozambique [18] and other African countries such as Kenya reported G3P [8] and G9P [8] [44].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in concordance with reports of African countries such as Botswana and Kenya in which G3P [4] was found after rotavirus vaccine introduction [42,43]. However, some studies reported G3P [8] in high frequency in cases of MSD in the post-vaccine introduction period in Mozambique [18] and other African countries such as Kenya reported G3P [8] and G9P [8] [44].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we have shown that G3 rotaviruses that re-emerged in 2017 in Malawi, almost twenty years after their last detection, became the predominant strains post-Rotarix vaccine introduction after replacing G1 and G2 rotaviruses as typical human strains. This finding is unique and in contrast with observations seen in most countries, including Australia, Italy, Hungary, Spain, Japan and Kenya where the emergence of G3 strains has mostly been due to equine-like G3 strains (Komoto et al 2018; Dóró et al 2016; Cowley et al 2016; Luchs et al 2019; Esposito et al 2019; Mwanga et al 2020). Through whole-genome sequencing, we showed that the re-emergence of G3 strains in Malawi was not associated with a single genotype, but rather four genotype variants; G3P[4] and G3P[6] with a DS-1-like constellation, G3P[8] with a Wa-like constellation and G3P[4] genotypes with a DS-1-like backbone containing a reassortant Wa-like NSP2 genome segment.…”
Section: Discussioncontrasting
confidence: 67%
“…The detection rates of G3 strains and other sporadically circulating genotypes has increased especially in countries using Rotarix rotavirus vaccine globally (Carvalho-Costa et al 2019; Wahyuni et al 2021; Roczo-Farkas et al 2018). While genotype G3 was not common in the African continent before rotavirus vaccine introduction, these strains have been reported in several African countries post-vaccination (Mhango et al 2020; Mwanga et al 2020; João et al 2020). Our previous work reported the prevalence of rotavirus strains circulating in Blantyre, Malawi from 1997 to 2019 (Mhango et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This shift in the age of rotavirus disease towards slightly older children has also been reported in other countries that have introduced rotavirus vaccines [ 26 , 29 ]. The equine-like G3P[8] variant was also reported by Mwanga et al, from the Kilifi region of Kenya in 2018; four years after Rotarix was introduced [ 30 ]. During this surveillance year, G3P[8] was the dominant genotype detected and the equine variant accounted for a small proportion of these G3P[8] cases, replacing G2P[4] and G1P[8] which had been predominant in the prior two years [ 30 ].…”
mentioning
confidence: 81%
“…The equine-like G3P[8] variant was also reported by Mwanga et al, from the Kilifi region of Kenya in 2018; four years after Rotarix was introduced [ 30 ]. During this surveillance year, G3P[8] was the dominant genotype detected and the equine variant accounted for a small proportion of these G3P[8] cases, replacing G2P[4] and G1P[8] which had been predominant in the prior two years [ 30 ]. The epidemiological trends of enteric viruses pre- and post-rotavirus vaccine introduction were investigated in this region by Lambisia et al, describing rotavirus, norovirus (genogroup GII), adenovirus, astrovirus and sapovirus [ 31 ].…”
mentioning
confidence: 81%